Chronotype’s effect on academic achievement and absence from classrooms and clinical sessions among clinical phase medical students at the Faculty of Medicine, University of Tabuk, Saudi Arabia - Alblewi, Sawsan Mohammed; Mirghani, Hyder (Frontiers in Psychology, 2025)
ObjectivesChronotype refers to an individual’s unique biological clock determined by bedtime preferences and daytime activities. The contradiction between sleep preferences and daily routines (circadian misalignment) could affect academic performance among students. This important issue has been a topic of considerable debate. We aimed to assess the chronotype’s effect on academic achievement and absence from classrooms and clinical sessions among medical students at the University of Tabuk.MethodsA cross-sectional study was conducted among 224 medical students at the University of Tabuk, Saudi Arabia, from March 2024 to August 2024. A structured Web-based questionnaire was designed based on the Morningness-Eveningness Questionnaire (MEQ), age, absence from classrooms and clinical sessions, and the cumulative grade average (GPA). Data analysis was conducted using the Statistical Package of the Social Science Software (SPSS), version 20, New York.ResultsOut of the 224 medical students (age 23.29 ± 1.87 years), 61.2% were categorized as having an intermediate chronotype, while 23.2% were identified as moderate evening chronotypes. Moderate morning and definite evening chronotypes were reported in 11.2 and 4.5%, respectively. A negative correlation was found between classroom absenteeism and GPA (95% CI, 0.053–0.749, p-value, 0.017). A positive correlation was found between students’ age and GPA (95% CI, 1.308–1.971, p-value, 0.000). No association was evident between the GPA, time of the study (95% CI, 0.648–3.660, p-value, 0.0329), and chronotype (95% CI, 0.931–1.004, p-value, 0.079).ConclusionMedical students at the University of Tabuk in Saudi Arabia were predominantly identified as intermediate and evening chronotypes. The chronotype was associated with classroom absenteeism and GPA. Further multicenter studies investigating the determinants of chronotypes are recommended.